2023
DOI: 10.1096/fj.202300414r
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate toxicity and SERCA2a dysfunction in sudden cardiac arrest

Abstract: Almost half of the people who die from sudden cardiac arrest have no detectable heart disease. Among children and young adults, the cause of approximately one-third of deaths from sudden cardiac arrest remains unexplained after thorough examination. Sudden cardiac arrest and related sudden cardiac death are attributed to dysfunctional cardiac ion-channels. The present perspective paper proposes a pathophysiological mechanism by which phosphate toxicity from cellular accumulation of dysregulated inorganic phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Indeed, it has been shown in skeletal muscle that calcium reuptake into the sarcoplasmic reticulum and myofiber relaxation is delayed if phosphate accumulates [275]. Furthermore, it has been shown that phosphate accumulations in the heart might interfere with normal calcium handling, leading to cardiac arrhythmias and sudden cardiac arrest [276].…”
Section: Phosphate and Sarcopeniamentioning
confidence: 99%
“…Indeed, it has been shown in skeletal muscle that calcium reuptake into the sarcoplasmic reticulum and myofiber relaxation is delayed if phosphate accumulates [275]. Furthermore, it has been shown that phosphate accumulations in the heart might interfere with normal calcium handling, leading to cardiac arrhythmias and sudden cardiac arrest [276].…”
Section: Phosphate and Sarcopeniamentioning
confidence: 99%